2017
DOI: 10.1007/s10902-017-9905-7
|View full text |Cite
|
Sign up to set email alerts
|

Economic Freedom, Income Inequality and Life Satisfaction in OECD Countries

Abstract: Since Piketty's Capital in the 21st Century in 2014, scientific interest into the impact of income inequality on society has been on the rise. However, little is known about the mediating role of income inequality in the relationship between market institutions and subjective well-being. Using panel analysis on a sample of 21 OECD countries to test the effects of five different types of economic freedom on income inequality, we find that fiscal freedom, free trade and freedom from government regulation increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 87 publications
(96 reference statements)
2
40
0
Order By: Relevance
“…In his analysis, this concern is addressed by the freedom observations being prior in time to all of the income equality observations. Similar strategy is used by Adam (2008), Galor, Moav, and Vollrath (2009), Nilsson (2010, 2014), Becerra et al (2012), Ezcurra and Rodríguez-Pose (2013), Bennett and Nikolaev (2017), Graafland and Lous (2018) in the related literature. Following this vein, we also replicate the analysis by regressing income inequality on lagged globalization and country risk.…”
Section: The Basic Discoverymentioning
confidence: 89%
See 1 more Smart Citation
“…In his analysis, this concern is addressed by the freedom observations being prior in time to all of the income equality observations. Similar strategy is used by Adam (2008), Galor, Moav, and Vollrath (2009), Nilsson (2010, 2014), Becerra et al (2012), Ezcurra and Rodríguez-Pose (2013), Bennett and Nikolaev (2017), Graafland and Lous (2018) in the related literature. Following this vein, we also replicate the analysis by regressing income inequality on lagged globalization and country risk.…”
Section: The Basic Discoverymentioning
confidence: 89%
“…While Berggren (1999) discusses the importance of detecting the potential reverse causality, their empirical results indicate no serious problem of endogeneity. However, some recent studies argue that globalization may well be both a cause and an effect of inequality (see, for example, Gradstein, 2007;Bergh & Nilsson, 2010Graafland & Lous, 2018). In this regard, one concern in our current specifications may be the endogeneity problem due to potential reverse causality from income inequality to globalization.…”
Section: The Basic Discoverymentioning
confidence: 96%
“…For example, long-term orientation may be causally dependent on economic freedom, as economic freedom may provide incentives for individuals to make long-term investments and plan for the future. Another relevant opportunity for future research is to distinguish between different dimensions of economic freedom to examine potential heterogeneous institutional effects on well-being (Graafland and Compen 2015;Graafland and Lous 2018). Furthermore, the focus on OECD countries reduces the heterogeneity between the countries studied.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rigobon and Rodrik (2005) found that trade openness reduces income levels, whereas Kagan, Gunningham and Thornton (2003) found that regulation has been directly responsible for the significant reductions in pulp mill pollution. Furthermore, Graafland and Compen (2015) found that small government may lower life satisfaction, whereas Graafland and Lous (2018) found a negative relationship between life satisfaction and small government, free trade and low government regulation.…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation